POC06 "YOU'LL HAVE TO SPEAK UP DOC…" an unusual after-effect of interventional neuroradiology. Issue 11 (22nd October 2010) - Konduri, R; Powell, R; Hughes, T A T; Halpin, S; Pickersgill, T P
Abstract : An obese 50-year-old man presented with new onset headache suggestive of raised pressure, diplopia, and hallucinations of unformed multicoloured images. A CT brain scan suggested a lesion consistent with an arteriovenous malformation in the right occipital lobe. MR imaging showed areas of midbrain and tectal plate signal change including the right medial geniculate body (MGB). CT venography revealed occlusion of the internal cerebral veins, the vein of Galen and the straight sinus. Conventional angiography delineated a complex AV dural fistula (AVDF), which was subsequently embolised. 48 h postembolisation he became profoundly deaf. Further MR imaging showed progression of the midbrain high signal to both MGBs. Concurrently a clinical diagnosis of obstructive sleep apnoea (OSA) was confirmed by investigation. The syndrome of Tectal Deafness is classically caused by lesions in the inferior colliculi which take projections from the MGBs. Embolisation of the AVDF may have worsened venous ischaemia by compromising venous outflow from the mesencephalon resulting in bilateral MGB ischaemia and deafness. The OSA may have contributed to the venous sinus thrombosis.